Analisis Gaya Belajar pada Taruna Teknika dalam Perkuliahan Fisika Terapan Sub Materi Fluida sebagai Bentuk Penerapan Pembelajaran Berdiferensiasi - Lusiani Lusiani; Andi Hendrawan; Fajar Firmansyah; Supriyanto Supriyanto (SAINTARA, 2023)
An educator should understand the learning style of each student, this is because an individual's learning style can be different from other individuals. The differences in learning styles must be managed properly so that learning objectives can be achieved. The problem with lectures is that most educators do not know that there are differences in individual learning styles and do not manage them properly. The purpose of this study is to analyze the Learning Styles of Technical Cadets in Applied Physics Lectures in Fluid Sub Material as a Form of Differentiated Learning Application. This study uses a combination research method between observation and literature review. The author takes a location in the AMN Cilacap Engineering Study Program by utilizing instruments in the form of 2 media, namely Google Forms and Mentimeter. It was concluded that the analysis of Learning Styles in Technical Cadets in Applied Physics Lectures in the Sub Material of Fluids as a Form of Differentiated Learning Application obtained the value that the choice of learning style in the first order is the choice of Auditory learning style, while the choice of learning style in the second order is the choice of the Visual learning style and the choice of style learning in the third or last order, namely the choice of Kinesthetic learning styles. Analysis of the choice of learning styles can be used as a form of implementing differentiated learning.